20-Hydroxyecdysone Primes Innate Immune Responses That Limit Bacterial and Malarial Parasite Survival in Anopheles gambiae - Rebekah A. Reynolds (American Society for Microbiology, 2020)
ABSTRACT Blood feeding is an integral behavior of mosquitoes to acquire nutritional resources needed for reproduction. This requirement also enables mosquitoes to serve as efficient vectors to acquire and potentially transmit a multitude of mosquito-borne diseases, most notably malaria. Recent studies suggest that mosquito immunity is stimulated following a blood meal, independent of infection status. Since blood feeding promotes production of the hormone 20-hydroxyecdysone (20E), we hypothesized that 20E plays an important role in priming the immune response for pathogen challenge. Here, we examine the immunological effects of priming Anopheles gambiae with 20E prior to pathogen infection, demonstrating a significant reduction in bacteria and Plasmodium berghei survival in the mosquito host. Transcriptome sequencing (RNA-seq) analysis following 20E treatment identifies several known 20E-regulated genes, as well as several immune genes with previously reported function in antipathogen defense. Together, these data demonstrate that 20E influences cellular immune function and antipathogen immunity following mosquito blood feeding, arguing the importance of hormones in the regulation of mosquito innate immune function. IMPORTANCE Blood feeding is required to provide nutrients for mosquito egg production and serves as a mechanism to acquire and transmit pathogens. Shortly after a blood meal is taken, there is a peak in the production of 20-hydroxyecdysone (20E), a mosquito hormone that initiates physiological changes, including yolk protein production and mating refractoriness. Here, we examine additional roles of 20E in the regulation of mosquito immunity, demonstrating that priming the immune system with 20E increases mosquito resistance to pathogens. We identify differentially expressed genes in response to 20E treatment, including several involved in innate immune function as well as lipid metabolism and transport. Together, these data argue that 20E stimulates mosquito cellular immune function and innate immunity shortly after blood feeding.